Strengthening Public Financial Governance through Village Facilitators: Evidence from Village Fund Management in Indonesia - Sonny, Sonny; Syauqi, Ahmad; Lubis, Iman (Indonesian Financial Review, 2025)
This study examines the role of Village Facilitators in strengthening public financial governance through the implementation of government financial policy in village fund management. Using a qualitative approach based on observations, in-depth interviews, focus group discussions, and document analysis, the study explores how facilitators enhance accountability, transparency, and allocative efficiency in decentralized financial systems. The findings show that Village Facilitators act not only as administrative supervisors but also as strategic intermediaries who translate financial regulations into practical governance mechanisms. Through social mapping, participatory planning, and community organization, they improve financial decision-making and accountability structures. However, challenges such as political dynamics, limited institutional capacity, and uneven digital literacy constrain effectiveness. This study highlights the importance of intermediary actors in linking financial policy and governance outcomes to achieve sustainable and accountable public financial management.